Queer Economics: Same-Sex Marriage Rate vs. Economics Crisis Expectation - Jiayu Li (Journal of World Economy, 2024)
Marriage is not just a promise between two individuals; it serves as a bridge between two families and provides the nurturing ground for many new lives. Research studies have indicated that marriage can enhance the subjective well-being of married individuals[i]. However, beneath the weighty commitments and responsibilities, the dissolution of marriage can increase illness rates and psychological distress among divorced women. [ii]While mainstream society still upholds the social stability brought by marriage and advocates it as an indispensable part of the human lifecycle, people are actively exploring alternative romantic relationships or family models, such as cohabitation. Many individuals engage in cohabitation as a prelude to formal marriage, viewing it as an experimental version of married life, enjoying the everyday romantic relationship without the legal costs and property entanglements. [iii]This article considers cohabitation as an alternative to marriage, which can also be understood as a substitution in consumption when people are deterred from marriage due to the high costs associated with divorce. Therefore, strategies people adopt towards marriage are often influenced by changes in societal patterns and the turbulence in politics and the economy. In comparison to heterosexual couples, the dynamics of marriage are more complex for same-sex couples. Apart from the ethical debates surrounding same-sex marriage, economic models have also demonstrated that same-sex marriage poses significant secular challenges. [iv]For instance, issues like post-marriage healthcare for same-sex couples and the impact of their married status on the labor market are still subjects of debate. However, these issues primarily target the challenges and research pertaining to the identity of being a same-sex individual. Nevertheless, as members of society, same-sex couples also experience the fluctuations brought about by broader social cycles, such as the impact of economic crises. There is relatively limited research in the field on how same-sex couples respond to widespread societal crises, and the strategies employed by same-sex couples during different economic crises can effectively reflect the natural state of this community within society.[v] [i] Janice K Kiecolt-Glaser and Tamara L Newton. (2001). Marriage and Health: His and Hers. American Psychological Association. https://psycnet.apa.org/record/2001-01085-002. [ii] Frederick O Lorenz et al. (2006). The Short-Term and Decade-Long Effects of Divorce on Women’s Midlife Health. American Sociological Association. https://journals.sagepub.com/doi/abs/10.1177/002214650604700202. [iii] Brandon G Wagner, Kate H Choi, and Philip N Cohen. (2020). Decline in Marriage Associated with the COVID-19 Pandemic in the United States. Sage Journals. https://journals.sagepub.com/doi/10.1177/2378023120980328. [iv] DOUGLAS W ALLEN. (2006). An Economic Assessment of Same-Sex Marriage Laws. Semantic scholar. https://www.semanticscholar.org/paper/An-Economic-Assessment-of-Same-Sex-Marriage-Laws-Allen/513a92f3d397ae2b787094294aa465d48053ef53. [v] Malaczewska Paulina and Malaczewski Maciej. (1970, January 1). Marriage, Divorce and Coronavirus—Theoretical Analysis of the Influence of COVID-19 on Family Capital. Economics and Business Review. https://ideas.repec.org/a/vrs/ecobur/v8y2022i3p126-142n7.html.